2018
DOI: 10.29088/gmjm.2018.58
|View full text |Cite
|
Sign up to set email alerts
|

Nano-phytosome of Quercetin Could Protect Liver from Plasmodium Berghei in Mouse Model

Abstract: Background and purpose: Malaria is one of most important diseases especially in tropical regions. Flavonoids are known to have beneficial properties that could be profitable. This study aimed to evaluate the effects of nano-phytosomes of Quercetin (NQ) on liver damages of mice infected with Plasmodium berghei. Methods: A total of sixty male BALB/c mice were intra-peritoneally infected by administration of 10 6 P.berghei-infected RBCs. Animals were acclimatized for 7 days and divided into 5 groups including 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Davoodi et al [ 79 ] observed that Que nanophytosomes (NQ; 10 mg/kg) substantially reduced histopathological damage (e.g., Kupffer cell hyperplasia, hepatic necrosis, hemosiderosis, and periportal inflammation) and serum levels of both IL-1 β and TNF- α in P. berghei -infected mice. Moreover, the best results were achieved when NQ (10 mg/kg) was applied in combination with hydroxychloroquine sulfate (2 mg/kg).…”
Section: Plasmodium Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…Davoodi et al [ 79 ] observed that Que nanophytosomes (NQ; 10 mg/kg) substantially reduced histopathological damage (e.g., Kupffer cell hyperplasia, hepatic necrosis, hemosiderosis, and periportal inflammation) and serum levels of both IL-1 β and TNF- α in P. berghei -infected mice. Moreover, the best results were achieved when NQ (10 mg/kg) was applied in combination with hydroxychloroquine sulfate (2 mg/kg).…”
Section: Plasmodium Sppmentioning
confidence: 99%
“…Flavonoids could also act synergistically with the existing antiparasitic drugs. For example, Que, even at low concentrations, have already been demonstrated to boost therapeutic potential of antimalarial drugs such as chloroquine or artemisinin [ 52 , 55 , 79 ]. Moreover, the synergism between Que and antiparasitic drugs could diminish the development of drug-resistant pathogens in response to these compounds.…”
Section: Future Directionsmentioning
confidence: 99%